IMPLEMENTASI LAYANAN KOMPONEN KESEHATAN PADA PROGRAM KELUARGA HARAPAN (Studi Kasus di Kecamatan Slogohimo Kabupaten Wonogiri Tahun 2022) - Dina Ayu Lestari, Dina; Rahardjo, Budhi; Johar, Syefira Ayudia (Universitas Veteran Bangun Nusantara, 2024)
ABSTRACT Based on observations made in Slogohimo District, KPM data for 2020 was 1,985 KPM (Family Hope Program), in 2021 it rose 3.58% to 2,056 KPM, and in 2022 it also rose 17.51% to 2,416 KPM. The number of stunted toddlers ranks 3rd in Wonogiri Regency and will reach 13% in 2022 and the maternal mortality rate (MMR) in 2022 will be 11% because the quality of life of the community is still low. The number of pregnant women was 212 people, 115 postpartum mothers and 154 mothers with toddlers. The aim of the research is to describe the implementation, impact and inhibiting and supporting factors of PKH on health components (pregnant women, breastfeeding mothers, postpartum mothers, early childhood in Slogohimo District, Wonogiri Regency in 2022. This type of research is qualitative research with a descriptive approach. The subjects of this research were 7 informants (PKH coordinators and assistants, posyandu cadres and 4 KPM health components). The research instrument uses interview guides, observation sheets, recording equipment and documentation. The results of the research show that the implementation of the health component of PKH has not gone well because there are still some poor people who do not receive PKH assistance and the distribution of aid funds is often late, so that KPM as aid recipients also experience financial difficulties to meet their daily needs. The positive impact of the program is that it is useful for meeting the needs of KPM, changing behavior and family independence. The negative impact is that KPM becomes dependent on aid and the use of aid is not according to its intended purpose. The advice for PKH actors is to always update data by proposing KPM candidates who meet the requirements to the Social Service so that assistance is provided on target and monitoring in the field to find out that aid funds are spent according to the needs of pregnant women, breastfeeding mothers, postpartum mothers and early childhood. Keywords: Implementation, Services, Health Components, Family Hope Programs